Perancangan Sistem E-Commerce “Thrift Mart” Berbasis Web dengan Metode Waterfall - Muh Abdul Aziz Nasuha; Ika Ayu Pertiwi; Fathin Rifsya Fadhillah; Munfarid Zulkahfi (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2024)
With the rapid growth of the fashion industry, textile waste and its environmental impact have significantly increased. In response, the culture of thrifting has emerged as a sustainable consumption alternative. However, online secondhand trading still faces several challenges, including limited product features, lack of product transparency, and poor transaction and customer satisfaction management. This study aims to design and develop a web-based e-commerce system called ThriftMart to facilitate secure and efficient secondhand transactions. The system was built using the Waterfall methodology, which includes requirement analysis, system design, development, testing, and maintenance phases. Laravel and MySQL were utilized as the main technologies, supporting features such as product management, ordering, payment processing, customer reviews, multi-role dashboards, and real-time notifications. Testing results indicate that all core features function properly and meet user expectations. The system’s development has implications for promoting circular economy practices, improving operational efficiency in thrift businesses, and supporting the digital transformation of MSMEs in the secondhand fashion sector. This application is expected to strengthen a more sustainable and environmentally friendly digital thrift ecosystem in Indonesia.